Beethoven Monument in Bonn - Mehl, F. (engraver):::Creator::::::::::::; Hähnel, Ernst Julius, 1811-1891 (sculptor):::Contributor::::::::::::
Engraving of the Beethoven Monument sculpted by Ernst Julius Hähnel, and the surrounding plaza in Bonn.